Human virology : a text for students of medicine, dentistry, and microbiology - Collier, L. H; Oxford, John; Pipkin, Jim (Oxford University Press, 2000)
This is the second edition of a well received textbook which was originally published in 1993. The new edition includes major revisions in certain chapters, and integrates the interface between science and medicine more than it did previously. There is also more discussion on clinically important conditions. The bright, bold format, from the first edition has been kept, but has been given a more sophisticated and up-to-date look. Virology, perhaps more than any other discipline, plays an extremely important role in the advances of biomedical research. New discoveries are continually being made, and their subsequent application to the relief of suffering proceed at an ever-increasing pace. Virology is important not only in the study of infections and their treatment and prevention, but also in the unravelling of the most fundamental aspects of biology. This is because viruses have an intimate relationship with the basic machinery of their host cells. Thus, research on how viruses reproduce themselves and spread has given us many insights into the way in which the cells of our bodies function, leading in turn to a better understanding of the whole organism and of how infective diseases may be prevented or cured.The speed of advance in this area has increased the difficulties encountered by students and teachers in absorbing and imparting important information as effectively as possible. It is important that the students are provided with enough information not just to pass examinations but also to provide a foundation of knowledge adequate for subsequent professional practice. It is equally important that this information is presented in an attractive assimilated manner. In this book Leslie Collier and John Oxford present a delightfully written account of basic and clinical virology that meets both of these requirements. Richly illustrated with around 130 line drawings and photographs, Human virology provides a complete review of this rapidly expanding field of biology for medical, dental, and microbiology students.
Keywords: virové nemoci; Virus Diseases; Viruses; viry; replikace viru; Virus Replication; virologie; Virology